Reclaiming the Xhotsa: climate adaptation and ecosystem restoration via the return of Sumas Lake - Finn, Riley J. R.; Ned - Kwilosintun, Murray; Ballantyne, Leah; Hamilton, Ian; Kwo, Janice; Seymour-Hourie, Rayanna; Carlson, Deborah; Walters, Kristen E.; Grenz, Jennifer; Martin, Tara G. (Frontiers in Conservation Science, 2024)
Sumas Lake (Xhotsa), located in the Fraser Valley, British Columbia, Canada, was the heart of Semá:th Nation Territory and the epicenter of a complex Indigenous food system. For the Semá:th people, the lake represented life and livelihood. In 1924, the lake was stolen and drained in an instance of land theft that occurred during a nationwide campaign of land dispossession and genocide, decimating an ecology that supported a rich and diverse Indigenous food system and replacing it with a settler food system. A century later, in November 2021 climate change induced flooding caused the lake to return, resulting in the evacuation of thousands of people and causing millions in damages to homes and infrastructure. Since the flood, the response has been a continuation of the status quo to protect settler agricultural lands via increased investment in hard structures that control the flow of water based on assumptions of the predictability of future flow conditions. We offer a missing narrative by bringing together an analysis of Indigenous laws and oral tradition with an assessment of the economic costs of “managed retreat”, defined as the purposeful relocation of people and infrastructure out of harm’s way. We find that the cost of buying out properties in the lakebed and allowing the lake to return is close to half the cost ($1 billion) of maintaining the status quo ($2.4 billion), while facilitating climate adaptation, and restoration of a floodplain ecosystem that supported thriving populations of people, salmon, sturgeon, ducks and food, and medicinal plants-- including many species which are now endangered. Returning Sumas Lake by centering ‘WaterBack’ as a climate resiliency solution, enacts both food systems and ecological reconciliation, addressing the harms caused by the loss of the lake to the Semá:th People that is still felt to this day. In a time when climate change induced flooding is predicted to increase, this study demonstrates how the inclusion of Indigenous laws and knowledges are critical to the development of solutions toward a more sustainable and just future.